Assessing and strengthening community‐based coastal governance - Mark Andrachuk; Graham Epstein; Shauna Mahajan; Zephania Arnold; Sinezio Junior; Dresy Lovasoa; Monalisa Mabandla; George W. Maina; Caroline Njeri; Samson Obiene; Geoffrey Odhiambo; Lenice Ojwang; et al. (Conservation Biology, 2026)
Community‐based coastal governance is essential for biodiversity conservation and sustainable livelihoods, yet many communities continue to face significant challenges in establishing and sustaining effective governance systems. We sought to improve understanding of the current status of community‐based coastal governance across five countries in the Southwest Indian Ocean (SWIO) region of Africa. Using the Elinor tool and data system, we examined how specific governance attributes relate to perceived social and ecological outcomes and sought insights for community‐managed areas (CMAs) in the SWIO region. Progress toward strong community‐based governance of CMAs has been uneven across the region and across governance attributes. Although some CMAs have established clearly defined management boundaries and property rights, many other CMAs are still working to improve some attributes, such as congruent regulations, transparency, accountability, and operational capacity. Perceived ecological and social outcomes correlated with different governance attributes. Perceived ecological outcomes were positively correlated with measures of property rights and local governance, whereas perceived social outcomes were correlated with local governance and operational capacity. The strength of CMA governance tended to improve in the first 5–10 years after establishment, then governance attributes plateaued or declined thereafter. These findings coincide with typical funding cycles, thus reinforcing the value of continued investment in community‐based coastal governance. Specifically, our findings point to the importance of providing long‐term capacity development and securing durable conservation finance to ensure the success of CMAs. More broadly, these findings contribute to a growing body of evidence of the importance of paying attention to when and how to leverage different types of support and capacity building.

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Understanding of Sustainable Development Goals among communities living adjacent to mangroves in Kenya - Samson Obiene; Khamati Shilabukha; Geoffrey Muga; Lenice Ojwang; Margaret A. Owuor (Western Indian Ocean Journal of Marine Science, 2022)
Mangroves are among the most productive ecosystems, known for their diverse provisioning, regulating, supporting and aesthetic services. The ecosystem directly supports livelihoods and ensures food security and nutrition of people through its ecosystem services (ES) such as wood, fish and medicines while protecting them by stabilizing shorelines, reducing flooding, and mitigating climate change and natural disasters such as tsunamis. In so doing, the ecosystem promotes several sustainable development goals (SDGs) and co-benefits several others. This relationship however remains under explored with limited studies on the co-benefit scenarios and the cognitive views of mangrove resource users. This paper highlights gaps in knowledge of the role of mangroves in development and the implications on ecosystem governance. The study analysed the ‘ideal’ scenario presented in secondary data in comparison to community perspectives on mangrove-related development. Bearing in mind the complexity of the concept of sustainability, development was categorised at local, national and international levels, and community members were asked to mention any known links to mangrove ES at any of the three levels. Results indicate that 45.4 % (n=166) of the community understood the roles of mangroves in development. The majority (79.5 %) were able to link the ecosystem to local (village level) development, 43.1 % to both local and national development while only 13.5 % could link the ecosystem to local, national, and international development. Forty-three per cent (n=157) of the community did not know of the relationship between mangroves and development while 11.6 % (n=43) felt that mangroves do not contribute to development. The study further disaggregated this knowledge socio-demographically, highlighting opportunities for enhancing governance, conservation and the use of mangrove ecosystems in Kenya.